Synthesis 3-(2-propyne-OXY)-1,2: 6,6-di-O-isopropylidene-Î±- D-gluco ranse and react with secondary amine ((Ma nich reaction)) - M.N . Mohamad (Al-Qadisiyah Journal of Pure Science, 2017)
The aim of the present work is the synthesis of acetylen sugar, having acetyten group at position (3) the acelyenlce either derirative was left to react with secondary amine in the presence para formaldehyde (mannich - reaction )